FePt icosahedra with magnetic cores and catalytic shells - Wang, Rongming; Dmitrieva, Olga; Farle, Michael; Dumpich, Güntner; Acet, Mehmet; Mejía Rosales, Sergio; Pérez Tijerina, Eduardo Gerardo; Yacamán, Miguel José; Kisielowski, Christian (American Chemical Society, 2009)
Surprisingly oxidation resistant icosahedral FePt nanoparticles showing hard-magnetic properties have been fabricated by an inert-gas condensation method with in-flight annealing. High-resolution transmission electron microscopy (HRTEM) images with sub-Angstrom resolution of the nanoparticle have been obtained with focal series reconstruction, revealing noncrystalline nature of the nanoparticle. Digital dark-field method combined with structure reconstruction as well as HRTEM simulations reveal that these nanoparticles have icosahedral structure with shell periodicity. Localized lattice relaxations have been studied by extracting the position of individual atomic columns with a precision of about (0.002 nm. The lattice spacings of (111) planes from the surface region to the center of the icosahedra are found to decrease exponentially with shell numbers. Computational studies and energy-filtered transmission electron microscopy analyses suggest that a Pt-enriched surface layer is energetically favored and that site-specific vacancies are formed at the edges of facettes, which was experimentally observed. The presence of the Pt-enriched shell around an Fe/Pt core explains the environmental stability of the magnetic icosahedra and strongly reduces the exchange coupling between neighboring particles, thereby possibly providing the highest packing density for future magnetic storage media based on FePt nanoparticles.